Computer forensics jumpstart - Solomon, Michael (Michael G.), 1963- (Wiley Publishing, Inc., 2011)
A guide to computer forensics provides information on such topics as conducting a forensics investigation, finding hidden data, capturing images, collecting and preserving computer evidence, and using computer forensic tools.